MOŽNOSTI POSUZOVÁNÍ EFEKTIVITY INVESTIC DO MODRO-ZELENÉ INFRASTRUKTURY V URBANIZOVANÉM ÚZEMÍ - Jan Kopp; Pavlína Hejduková; Michaela Hejplíková (Trendy v podnikání)
Effective rainwater management is often associated with the implementation of blue-green infrastructure. The use of blue-green infrastructure is declared as a new rainwater management system supporting water retention and quality in the urban landscape along with benefits for public space, adaptation to climate change and biodiversity. Assessing the effectiveness of investments in the blue-green infrastructure is a topical issue for both public administration and private investors. On the cost side, it is advisable to include not only the cost of building the water management infrastructure in the optimization of the solution, but also the contributions of natural capital, which is reflected in the provision of ecosystem services. The paper presents possible criteria for the assessment of the blue-green infrastructure and discusses their relevance and mutual compatibility. Four parameters were used for comparison: (1) land use during the implementation of the measure, (2) maximum rainwater runoff, (3) blue-green infrastructure coefficient and (4) average implementation costs. Based on the calculations for the model area, differences in the evaluation of different elements of the blue-green infrastructure are demonstrated with regard to their price, hydrological function and other benefits for the urbanized area. As our results showed, the effectiveness of the investment depends on the preferred effect of the measure. Methodologically, the question of assessing ecosystem services so that the assessment is compatible with the financial level of investments remains open.